Modulation of Synovial Fluid-Derived Mesenchymal Stem Cells by Intra-Articular and Intraosseous Platelet Rich Plasma Administration. (12th October 2016) - Muiños-López, Emma; Delgado, Diego; Sánchez, Pello; Paiva, Bruno; Anitua, Eduardo; Fiz, Nicolás; Aizpurua, Beatriz; Guadilla, Jorge; Padilla, Sabino; Granero-Moltó, Froilán; Prósper, Felipe; Sánchez, Mikel
Abstract : The aim of this study was to evaluate the effect of intra-articular (IA) or a combination of intra-articular and intraosseous (IO) infiltration of Platelet Rich Plasma (PRP) on the cellular content of synovial fluid (SF) of osteoarthritic patients. Thirty-one patients received a single infiltration of PRP either in the IA space (n = 14 ) or in the IA space together with two IO infiltrations, one in the medial femoral condyle and one in the tibial plateau (n = 17 ). SF was collected before and after one week of the infiltration. The presence in the SF of mesenchymal stem cells (MSCs), monocytes, and lymphocytes was determined and quantified by flow cytometry. The number and identity of the MSCs were further confirmed by colony-forming and differentiation assays. PRP infiltration into the subchondral bone (SB) and the IA space induced a reduction in the population of MSCs in the SF. This reduction in MSCs was further confirmed by colony-forming (CFU-F) assay. On the contrary, IA infiltration alone did not cause variations in any of the cellular populations by flow cytometry or CFU-F assay. The SF of osteoarthritic patients contains a population of MSCs that can be modulated by PRP infiltration of the SB compartment.